Tiny [videorecording (DVD)] : a story about living small - Mueller, Merete; Mueller, Merete; Smith, Christopher (Director) (First Run Features, 2014)
In recent years, many people are redefining their American Dream to focus on flexibility, financial freedom, and quality of life over quantity of space. These self-proclaimed "Tiny Housers" live in homes smaller than the average parking space, often built on wheels to bypass building codes and zoning laws. Tiny takes viewers inside six of these homes stripped to their essentials, exploring the owners' stories and the design innovations that make them work.